2022
DOI: 10.1186/s13054-022-03950-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors for success of awake prone positioning in patients with COVID-19-induced acute hypoxemic respiratory failure: analysis of a randomized controlled trial

Abstract: Background Awake prone positioning (APP) improves oxygenation in coronavirus disease (COVID-19) patients and, when successful, may decrease the risk of intubation. However, factors associated with APP success remain unknown. In this secondary analysis, we aimed to assess whether APP can reduce intubation rate in patients with COVID-19 and to focus on the factors associated with success. Methods In this multicenter randomized controlled trial, cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
2
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(119 citation statements)
references
References 35 publications
6
105
2
6
Order By: Relevance
“…They have found that patients with late APP (>24 h of HFNC initiation) had higher mortality than patients with early APP (45% vs. 26%, P =0.03). [47] Although these results should be considered exploratory, they are consistent with those obtained in the study by Ibarra-Estrada et al , [45] in which APP has been initiated at 11.1 h after HFNC initiation. Therefore, we suggest that APP should be initiated as soon as patients are indicated for HFNC treatment.…”
Section: Influential Factors On the Treatment Success Of Appsupporting
confidence: 89%
See 2 more Smart Citations
“…They have found that patients with late APP (>24 h of HFNC initiation) had higher mortality than patients with early APP (45% vs. 26%, P =0.03). [47] Although these results should be considered exploratory, they are consistent with those obtained in the study by Ibarra-Estrada et al , [45] in which APP has been initiated at 11.1 h after HFNC initiation. Therefore, we suggest that APP should be initiated as soon as patients are indicated for HFNC treatment.…”
Section: Influential Factors On the Treatment Success Of Appsupporting
confidence: 89%
“…In the large randomized controlled study by Ibarra-Estrada et al , [45] several predictors for treatment success have been reported within the first 3 days after admission. First, at the initiation of HFNC, a ROX index of >6.0 (the ROX index is the ratio of SpO 2 /FiO 2 to respiratory rate; it is a clinical score combining a single number of the three main parameters used to monitor a patient with acute hypoxemic respiratory failure) and d -dimer concentrations of <1.4 mg/dL have been associated with APP treatment success.…”
Section: Predictors Of Treatment Success On Appmentioning
confidence: 98%
See 1 more Smart Citation
“…Using a mean of pre-prone LUS score of 18.7 and standard deviation (SD) of 4.4 and post-supine LUS score at day 3 of 16.9 and SD of 4.6 [ 14 ], a confidence level (1-α) of 95% and power (1-ß) of 95%, the number of patients was 70. Considering an attrition rate of 5%, we calculated the total sample size as 74.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous cohort study of prone-positioning in intubated patients with COVID-19, we found that although most patients had an improvement in oxygenation on the first session of prone positioning, only those who survived had a significant response over the second and third sessions of prone positioning, which suggests that serial measurements along the first three days of treatment rather than the first session only, might improve the accuracy of prediction regarding patient-centered outcomes [ 13 ]. Moreover, in a large randomized controlled trial investigating the effects of APP on non-intubated patients with COVID-19, we found that LUS scores after three days of APP treatment decreased only in patients who eventually avoided intubation/death [ 14 ]. Therefore, we performed this study with two aims: 1) to explore the aeration response to APP in patients with AHRF induced by COVID-19 by using LUS within the first three days, and 2) to explore whether the changes in LUS associated with APP can predict the need for intubation.…”
Section: Introductionmentioning
confidence: 99%